1906
DOI: 10.2307/1272388
|View full text |Cite
|
Sign up to set email alerts
|

The Confederation and the Constitution, 1783-1789

Abstract: This The Confederation and the Constitution, 1783-1789 book is absolutely not ordinary book, you have after that it the world is in your hands. The benefit you receive by reading this book is information inside this reserve incredible fresh, you will get data which is getting deeper you read a lot of information you will get. This specific The Confederation and the Constitution, 1783-1789 without we know teach the one who looking at it become critical in considering and analyzing. Don't be worry The Confederat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

1982
1982
2002
2002

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 0 publications
0
4
0
Order By: Relevance
“…In closing, it should be pointed out that the rotation pulse for AI Dra and V505 Sgr both display within the errors of the observations the sinusoidal-like, symmetric shape that is expected for stars that approximate rigid rotating bodies with circular cross sections in eclipse. However, there have been frequent reports in the literature of eclipsing binaries whose rotation pulses are not symmetric (e.g., Worek 1985;Hube and Couch 1982;McLaughlin 1937). Verifying these cases, identifying others, and developing models to account for their asymmetries are this author's primary motives for investigating the Rossiter-McLaughlin rotation effect.…”
Section: Discussionmentioning
confidence: 99%
“…In closing, it should be pointed out that the rotation pulse for AI Dra and V505 Sgr both display within the errors of the observations the sinusoidal-like, symmetric shape that is expected for stars that approximate rigid rotating bodies with circular cross sections in eclipse. However, there have been frequent reports in the literature of eclipsing binaries whose rotation pulses are not symmetric (e.g., Worek 1985;Hube and Couch 1982;McLaughlin 1937). Verifying these cases, identifying others, and developing models to account for their asymmetries are this author's primary motives for investigating the Rossiter-McLaughlin rotation effect.…”
Section: Discussionmentioning
confidence: 99%
“…Published spectroscopic estimates of the spectral type of the brighter and hotter component of δ Lib are A0 V (Roman 1956;Sahade & Hernandez 1963;Tomkin 1978), whilst the photometry of Koch (1962) suggested a type not later than B9.5 V. The spectroscopy of Tomkin (1978) indicated that the cooler star has an early G spectral type, in agreement with Koch's (1962) expectations based on UBV photometry. Velocity curves of the primary E-mail: clh@ll.iac.es (CL); mam@ll.iac.es (MJA); claret@iaa.es (AC) component have been obtained by Schlesinger (1910), McLaughlin (1934) and Sahade & Hernandez (1963). Tomkin (1978) obtained the velocity curves of both stars, the first ever for the cool secondary component.…”
Section: Introductionmentioning
confidence: 99%
“…The Ha emission line has presented a long term variation (24-25 years) of its equivalent width (defined here as the surface of emission above the stellar continuum); this time scale is an intermediate value between those obtained respectively by Jessup (1932) andMcLaughlin (1949). For this determination additional data found in the literature were used.…”
Section: Spectroscopymentioning
confidence: 99%